Epigenetically Active Drugs Inhibiting DNA Methylation and Histone Deacetylation - A. Chistiakov, Dimitry; A. Myasoedova, Veronika; N. Orekhov, Alexander; V. Bobryshev, Yuri (Current Pharmaceutical Design, 2017)
Epigenetic mechanisms, which are involved in the regulation of gene expression, are tightly controlled. Loss of a proper epigenetic control can lead to global epigenetic alterations frequently observed in various diseases including cancer. Aberrant epigenetic changes induced in malignant cells lead to emergence of neoplastic properties, which inhibit cell differentiation and strict cell cycle control but greatly enhance stemness-related features. However, abnormal epigenetic patterns can be reversed by action of epigenetically active agents. Epigenetic machinery comprises a variety DNA/histone modifiers and chromatin remodelers. Chemical substances able to influence on the activity of epigenetic factors such as inhibitors of DNA methyltransferases or histone deacetylase inhibitors can be used as therapeutic agents for improving aberrant epigenetic signatures in cancer cells. Preclinical studies showed efficiency of such epigenetic drugs for the treatment of variety of cancers. So far, several epigenetically active compounds were approved for therapy of hematological malignancies. However, many challenges should be resolved for efficient use of epidrugs in the treatment of non-hematological solid tumors and advanced cancers associated with chemoresistance and higher risk of relapse.
Keywords: methylation